Manufacturing reshoring: A strategy to manage risk and commitment in the logic of the internationalization process model. Issue 1 (14th January 2019) - Ciabuschi, Francesco; Lindahl, Olof; Barbieri, Paolo; Fratocchi, Luciano
Abstract : Purpose: This paper aims to theorize on the internationalization process model to explain cases of manufacturing reshoring as decisions taken to manage risk when internationalizing. Design/methodology/approach: The paper is of a conceptual nature. Building on the logic of the internationalization process model, the authors extend previous work by focusing on firms' risk perception (determined by commitment, knowledge and uncertainty as key variables) to explain also reshoring decisions. Findings: Four propositions were developed, concerning the likelihood of firms to make manufacturing reshoring decisions. The first two propositions deal with the effects of new risk contingencies, and the other two refer specifically to the effects of managerial perceptions of three different typologies of risk, namely, host-country, home-country and reshoring-process specific risk. Originality/value: While reshoring has been discussed mainly on the basis of economic arguments, this paper offers an alternative, behavioural view of this phenomenon as a strategic risk-management process. Therefore, it offers initial steps to theorize about reshoring from a risk-management perspective and, in doing so, opens up a number of avenues for future research.